2018
DOI: 10.1093/jn/nxx031
|View full text |Cite
|
Sign up to set email alerts
|

n–3 Fatty Acid Supplementation in Mothers, Preterm Infants, and Term Infants and Childhood Psychomotor and Visual Development: A Systematic Review and Meta-Analysis

Abstract: n-3 PUFA supplementation improves childhood psychomotor and visual development, without significant effects on global IQ later in childhood, although the latter conclusion is based on fewer studies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
73
0
3

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(77 citation statements)
references
References 81 publications
(63 reference statements)
1
73
0
3
Order By: Relevance
“…Nevertheless, despite intensive research in the area of fatty acid supplementation, no conclusive evidence exists thus far regarding child neurodevelopment or cognition and visual outcomes (reviewed in ref. 22,30 ), the benefits mainly manifested in preterm born infants 31 . In agreement with our study, although in that other publication, the child's development was evaluated by a psychological test, Mendez and co-workers 32 found that maternal fish consumption in excess of two to three times per week was associated with higher test scores when the child was four years old.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, despite intensive research in the area of fatty acid supplementation, no conclusive evidence exists thus far regarding child neurodevelopment or cognition and visual outcomes (reviewed in ref. 22,30 ), the benefits mainly manifested in preterm born infants 31 . In agreement with our study, although in that other publication, the child's development was evaluated by a psychological test, Mendez and co-workers 32 found that maternal fish consumption in excess of two to three times per week was associated with higher test scores when the child was four years old.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical trials of DHA supplementation and brain function N-3 LCPUFAs supplementation is recommended worldwide for fetomaternal and maternal-childhood growth and development, and cognitive function of the child (Carlson et al, 2013;Julvez et al, 2016;Koletzko et al, 2007;Parra-Cabrera et al, 2011). DHA supplementation improved pregnancy outcome, gestation, reduction in early preterm and very low birth weight, childhood visual and psychomotor development (Carlson et al, 2013;Shulkin et al, 2018).…”
Section: Dha Deficiency and Human Brain Functionmentioning
confidence: 99%
“…DHA is especially important for optimal development during the first 6 months of life postpartum (Lauritzen et al 2016). In addition, DHA supplementation during late pregnancy and early infancy has been found to subtly improve infant neural development (Shulkin et al 2018). Although its precise role in brain functioning and cognition throughout life has not yet been fully defined or quantified, the high accretion rates (Kris-Etherton et al 2009) and the amount of DHA accumulated in the developing brain suggest that DHA is a vital component in central nervous system function.…”
Section: Introductionmentioning
confidence: 99%